2013
DOI: 10.1186/1471-2369-14-152
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics and prevalence of cardiovascular disease in newly visiting or referred chronic kidney disease patients to nephrology centers in Japan: a prospective cohort study

Abstract: BackgroundAbout 39,000 patients were newly prescribed renal replacement therapy in Japan in 2011, resulting in a total of more than 300,000 patients being treated with dialysis. This high prevalence of treated end stage kidney disease (ESKD) patients is an emergent problem that requires immediate attention. We launched a prospective cohort study to evaluate population specific characteristics of the progression of chronic kidney disease (CKD). In this report, we describe the baseline characteristics and risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 21 publications
(21 reference statements)
6
30
3
Order By: Relevance
“…In the Chinese cohort, urine protein was not significantly associated with CVD in CKD ( P  = 0.526) (Table 4). This is different from the results found in Japan [20] and US [21], where increased proteinuria was associated with a higher CVD prevalence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the Chinese cohort, urine protein was not significantly associated with CVD in CKD ( P  = 0.526) (Table 4). This is different from the results found in Japan [20] and US [21], where increased proteinuria was associated with a higher CVD prevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…Deserving additional attention is the prominence of cerebrovascular disease among C-STRIDE participants exhibiting CVD. This is similar to the findings of the ROUTE study (Japan) [20], but different from the MERENA (Spain) [5] and CRIC (USA) [21] studies, in which heart disease and PAD constituted the majority of CVD events. There are two possible explanations for the high incidence of cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 79%
“…The CKD‐ROUTE study was a prospective, observational cohort of a representative Japanese population with CKD G2–G5 who were not undergoing dialysis. Details of the study design have been previously reported . Over 1000 participants were enrolled at the Tokyo Medical and Dental University Hospital and its 15 affiliated hospitals in the Tokyo area.…”
Section: Methodsmentioning
confidence: 99%
“…At enrollment, the medical history and current medications for each patient were recorded. Blood and urine samples were collected to measure clinical variables . The estimated glomerular filtration rate (eGFR) was calculated using the modified three‐variable Modification of Diet in Renal Disease (MDRD) equation developed by the Japanese Society of Nephrology to adjust for Japanese physical characteristics: eGFR = 194 × serum creatinine −1.094 × age −0.287 (if female, ×0.739).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation